1981
DOI: 10.1007/bf02666054
|View full text |Cite
|
Sign up to set email alerts
|

High performance reversed‐phase chromatography of natural triglyceride mixtures

Abstract: High performance reversed-phase chromatography (HPRC) is an efficient and powerful tool gaining momentum in the separation of triglycerides and other lipid components. In the present study the effect of different variables in triglyceride separation has been studied. It was found that a longer hydrocarbon chain bonded to silica gel as well as the percent coverage improved the separation. Smaller particle size packing increased triglyceride resolution. A decrease in mobile phase polarity by increasing the aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…The mobile phase was a mixture of acetone-acetonitrile 1:1, v/v , and the flow rate was 0.8 mL/min. TAG molecular species were identified using equivalent carbon number ECN and theoretical carbon number TCN of TAGs as described in the literature 14,15 .…”
Section: Tag Molecular Species Compositionmentioning
confidence: 99%
“…The mobile phase was a mixture of acetone-acetonitrile 1:1, v/v , and the flow rate was 0.8 mL/min. TAG molecular species were identified using equivalent carbon number ECN and theoretical carbon number TCN of TAGs as described in the literature 14,15 .…”
Section: Tag Molecular Species Compositionmentioning
confidence: 99%
“…5 A . Judging from the Snyder s polar parameter 19 value of 0.1, 2.7, and 5.1 for hexane, benzene, and acetone, respectively, these results indicate that polarity of reaction solvents affects the lipase activity for acidolysis reaction. Domingo et al reported that, in lipase-catalyzed aza-Michael addition reactions, the target compounds were successfully synthesized in a non-polar hexane medium, whereas aminolysis side reaction proceeded in polar solvents 20 .…”
Section: Lipid Compositionmentioning
confidence: 90%
“…The mobile phase was a mixture of acetone/acetonitrile 1 : 1, v/ v , and the flow rate was 0.8 mL/min. TAG molecular species were identified using the equivalent carbon number and theoretical carbon number of TAGs, as described in the literature 18,19 . The area ratios of chromatograms were defined as the yields of each TAG generated by the acidolysis reaction.…”
Section: Lipid Compositionmentioning
confidence: 99%
“…Glyceryl tridecanoate was used as the internal standard. Herein, the TAG molecular species were identified using equivalent carbon number ECN 15 and theoretical carbon number TCN 16 of TAGs. For example, the ECN of ODO and tri-CLN-TAG were calculated as 26 and 36, respectively.…”
Section: Tag Compositionmentioning
confidence: 99%